2016
DOI: 10.5114/ada.2016.63884
|View full text |Cite
|
Sign up to set email alerts
|

Serum ghrelin levels in patients with Behcet’s disease

Abstract: IntroductionBehcet’s disease (BD) is a chronic, relapsing, systemic vasculitis of unknown etiology.AimTo measure serum ghrelin levels in BD patients and healthy controls and to investigate its association with metabolic syndrome (MetS).Material and methodsThirty BD patients and 30 healthy individuals were enrolled in the study. Ghrelin levels were measured in blood samples using ELISA.ResultsThe mean serum ghrelin level in BD patients (28.57 ±14.04) was significantly lower compared to healthy controls (40.72 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 41 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…The prevalence of MetS in patients with BD was reported in eight studies [14,[22][23][24][25][26][27]. Among the included studies, MetS was reported in 25.52% of patients with BD (366/1434), whereas only 16.50% were found to be affected by MetS in the non-BD group (66/400).…”
Section: Behcet's Disease and Metabolic Syndromementioning
confidence: 99%
“…The prevalence of MetS in patients with BD was reported in eight studies [14,[22][23][24][25][26][27]. Among the included studies, MetS was reported in 25.52% of patients with BD (366/1434), whereas only 16.50% were found to be affected by MetS in the non-BD group (66/400).…”
Section: Behcet's Disease and Metabolic Syndromementioning
confidence: 99%
“…There are conflicting results in terms of lipid profile in BD 32‐39 . Since lipid profile is closely related with insulin resistance, we evaluated it in our study and found it to be significantly lower in active BD patients.…”
Section: Discussionmentioning
confidence: 87%
“…When studies investigating IR in patients with BD are examined, they have certain limitations such as the small number of patients or the sample including obese patients 8,9,31‐39 . A subgroup analysis according to BMI was undertaken in only one study 35 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations